Advantages of Foxp3+ regulatory T cell depletion using DEREG mice. Issue 3 (26th October 2014) - Mayer, Christian T.; Lahl, Katharina; Milanez‐Almeida, Pedro; Watts, Deepika; Dittmer, Ulf; Fyhrquist, Nanna; Huehn, Jochen; Kopf, Manfred; Kretschmer, Karsten; Rouse, Barry; Sparwasser, Tim
Abstract Several mechanisms enable immunological self‐tolerance. Regulatory T cells (Tregs) are a specialized T cell subset that prevents autoimmunity and excessive immune responses, but can also mediate detrimental tolerance to tumors and pathogens in a Foxp3‐dependent manner. Genetic tools exploiting the foxp3 locus including bacterial artificial chromosome (BAC)‐transgenic DEREG mice have provided essential information on Treg biology and the potential therapeutic modulation of tolerance. In DEREG mice, Foxp3+ Tregs selectively express eGFP and diphtheria toxin (DT) receptor, allowing for the specific depletion of Tregs through DT administration. We here provide a detailed overview about important considerations such as DT toxicity, which affects any mouse strain treated with DT, and Treg rebound after depletion. Additionally, we point out the specific advantages of BAC‐transgenic DEREG mice including their suitability to study organ‐specific autoimmunity such as type I diabetes. Moreover, we discuss recent insights into the role of Tregs in viral infections. In summary, DEREG mice are an important tool to study Treg‐mediated tolerance and its therapeutic circumvention.